SISTEM INFORMASI PERSEDIAAN OBAT PADA PUSKESMASSERPONG 2 BERBASIS WEB - Rahmat Pangestu Widodo (2022)
Puskesmas Serpong 2 is a public health facility located in South Tangerang City. This Puskesmas has a section assigned to manage and manage drug data, namely the pharmaceutical section. Problems that are often faced are a lot of data on supplies, prescriptions, usage, and receipt of scattered drugs, drug data collection documents are never backed up online so they are vulnerable to malware, in making drug request reports still use conventional methods. This research will focus on building a system that can manage and manage drug data so that officers can create, search, update, delete, and print data in the drug inventory information system. This study implements the development of the waterfall model system and PIECES as a method for analyzing the system. This system is designed using UML as a visual system modeling method, PHP and Codeigniter as the programming language and framework used, and MySQL as the database. This drug inventory information system can assist in managing drug data so that officers' work becomes more efficient and effective.